Asymmetric reproductive isolation between two sympatric annual killifish with extremely short lifespans - Polačik, Matej; Reichard, Martin (PloS one, 2011)
BACKGROUND: Interspecific reproductive isolation is typically achieved by a combination of intrinsic and extrinsic barriers. Behavioural isolating barriers between sympatric, closely related species are often of primary importance and frequently aided by extrinsic factors causing spatial and temporal interspecific separation. Study systems with a severely limited role of extrinsic factors on reproductive isolation may provide valuable insights into how reproductive isolation between sympatric species is maintained. We used no-choice experimental set-up to study reproductive barriers between two closely related sympatric African killifish species, Nothobranchius furzeri and Nothobranchius orthonotus. These fish live in small temporary savannah pools and have complete spatial and temporal overlap in reproductive activities and share a similar ecology. PRINCIPAL FINDINGS: We found that the two species display largely incomplete and asymmetric reproductive isolation. Mating between N. furzeri males and N. orthonotus females was absent under standard experimental conditions and eggs were not viable when fish were forced to mate in a modified experimental setup. In contrast, male N. orthonotus indiscriminately mated with N. furzeri females, the eggs were viable, and offspring successfully hatched. Most spawnings, however, were achieved by male coercion and egg production and embryo survival were low. Behavioural asymmetry was likely facilitated by mating coercion from larger males of N. orthonotus and at relatively low cost to females. Interestingly, the direction of asymmetry was positively associated with asymmetry in post-mating reproductive barriers. SIGNIFICANCE: We showed that, in fish species with a promiscuous mating system and multiple matings each day, selection for strong mate preferences was relaxed. This effect was likely due to the small proportion of resources allocated to each single mating and the high potential cost to females from mating refusal. We highlight and discuss the fact that males of rarer species may often coercively mate with females of a related, more abundant species.
Keywords: rozmnožování; Reproduction; Sexual Behavior, Animal; Fundulidae; Male; Animals; Female; mužské pohlaví; ženské pohlaví; sexuální chování zvířat; zvířata